Sharia, Gender Politics, and Public Discourse: Media Representation of Female Royal Leadership in Yogyakarta - Nugroho, Catur; Huda, Muhammad Chairul; Wulandari, Astri; Nastain, Muhamad; Malau, Ruth Mei Ulina (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2025)
This article examines how two mainstream Indonesian newspapers—Kompas and Republika—construct competing discourses around the prospect of female royal leadership in the Yogyakarta Sultanate. Focusing on the 2015 succession controversy triggered by Sultan Hamengku Buwono X’s decision to open the throne to his eldest daughter, the study investigates how media narratives invoke Islamic law, royal tradition, and gendered authority. Using Norman Fairclough’s three-dimensional Critical Discourse Analysis, the article analyses news reports and opinion pieces published between March and May 2015 to uncover how linguistic choices, sources, and intertextual references are mobilised to legitimise or contest a woman’s claim to the throne. The findings show that Republika frames the issue through a conservative Sharia-based perspective, emphasising religious orthodoxy and patriarchal norms. On the other hand, Kompas adopts a more pluralist and constitutionalist framing that normalises female leadership as congruous with democratic and cultural change. The primary argument advanced in this article is that the core site of contention is not Islamic law per se, but the way Sharia is selectively interpreted and circulated through media discourse to support competing hegemonic projects concerning gender and authority. Theoretically, the study demonstrates that media discourse serves as a critical arena in which Sharia, gender authority, and cultural legitimacy are negotiated, thereby making an essential contribution to Islamic legal studies and critical media analysis.